Immunogenicity regulation of genetically engineered vaccine and its potential in tumor treatment - Yang, Zhuoran (Transactions on Materials, Biotechnology and Life Sciences, 2024)
In this study, the strategy of enhancing immunogenicity of genetically engineered vaccine and its application potential in tumor treatment were discussed. Firstly, the study explained the principle that genetic engineering vaccine designed antigen by gene recombination technology to trigger strong immune response. By adjusting gene combination, improving vaccine delivery system and using adjuvant, the immune stimulation ability and delivery efficiency of vaccine were improved. Especially in tumor therapy, these vaccines stimulate specific immune responses against specific or related tumor antigens. This paper also summarizes the clinical manifestations of mRNA cancer vaccine and individualized cancer vaccine, and discusses the combined application with traditional treatment methods such as chemotherapy, radiotherapy, targeted therapy and immune checkpoint inhibitors, in order to improve the treatment effect and the diversity of patients’ treatment options.